A Noninvasive Method to Reduce Radiotherapy Positioning Error Caused by Respiration for Patients With Abdominal or Pelvic Cancers. (19th July 2019) - Li, Weifeng; Jiang, Zhuoran; Chu, Kaiyue; Jin, Jianhua; Ge, Yun; Cai, Jing
Purpose: To develop an infrared optical method of reducing surface-based registration error caused by respiration to improve radiotherapy setup accuracy for patients with abdominal or pelvic tumors. Materials and Methods: Fifteen patients with abdominal or pelvic tumors who received radiation therapy were prospectively included in our study. All patients were immobilized with vacuum cushion and underwent cone-beam computed tomography to validate positioning error before treatment. For each patient, after his or her setup based on markers fixed on immobilization device, initial positioning errors in patient left-right, anterior-posterior, and superior-inferior directions were validated by cone-beam computed tomography. Then, our method calculated mismatch between patient and immobilization device based on surface registration by interpolating between expiratory- and inspiratory-phase surface to find the specific phase to best match the surface in planning computed tomography scans. After adjusting the position of treatment couch by the shift proposed by our method, a second cone-beam computed tomography was performed to determine the final positioning error. A comparison between initial and final setup error will be made to validate the effectiveness of our method. Results: Final positioning error confirmed by cone-beam computed tomography is 1.59 (1.82), 1.61 (1.84), and 1.31 (1.38) mm, reducing initial setup error by 24.52%, 51.04%, and 53.63% in patient left-right, anterior-posterior, and superior-inferior directions, respectively. Wilcoxon test showed that our method significantly reduced the 3-dimensional distance of positioning error ( P < .001). Conclusion: Our method can significantly improve the setup precision for patients with abdominal or pelvic tumors in a noninvasive way by reducing the surface-based registration error caused by respiration.